The influence of product quality, price, and location on customer satisfaction at Kopi Kulo Budiman Coffee Shop Balikpapan - Norhidayati Norhidayati; Ahmad Faid Maulana (International Journal of Applied Finance and Business Studies, 2023)
This study aims to determine the influence of product quality, price, and location on customer satisfaction at Kulo Budiman Balikpapan Coffee Shop. This research is based on a questionnaire survey. The sampling technique used purposive sampling with 93 respondents. The data analysis technique used multiple regression analysis. Based on the results of multiple linear regression analysis, it obtained a correlation coefficient (R) of 0.779 and a coefficient of determination (R2) of 0.607. Simultaneous test results (F-test) show that Fcount of 45.904 > F table of 2.71, meaning that product quality, price, and location simultaneously significantly influence customer satisfaction at Kulo Budiman Coffee Shop Balikpapan. Partial Test Results (t-test) indicate that the variable quality of the product (X1) t count of 2.015 > ttable 1.98667, which means that the product quality variable partially has a significant influence on customer satisfaction (Y), the price variable (X 2) shows tcount of 5.316 > ttable of 1.98667. This result shows that the price partially significantly influences customer satisfaction (Y). The location variable (X3) shows a tcount of 1951 < ttable of 1.98667. This result indicates that the location partially has no significant influence on customer satisfaction (Y).